Social Dynamics of the Pergulaan Village Community, Sei Rampah District, Serdang Bedagai Regency - Putri Nabila; Gracea Melvasari Aritonang; Diki Abdi Nugroho; Jimmy Saputra Tampuolon; Chindy Atika Wulan Dari Nasution (Medan Resource Center, 2026)
This article examines the rural history and social dynamics of Pergulaan Village, Sei Rampah District, Serdang Bedagai Regency, North Sumatra, with particular attention to its historical development as a settlement within the plantation landscape. The study addresses how the village's historical trajectory and socio-economic transformation have extended beyond its association with plantation activities by analyzing interactions between plantation and non-plantation residents, the diversity of local livelihoods, and patterns of change from the colonial era through the post-independence period to the present. Employing a library research approach, the study critically reviews and synthesizes data from official publications of Statistics Indonesia, official reports issued by the Serdang Bedagai Regency Government, institutional documents, and scholarly literature on plantation communities, rural social transformation, and village socio-economic development. The findings demonstrate that the village economy has consistently relied on a diversified occupational structure encompassing farming, livestock raising, small-scale trade, informal employment, and plantation-related work. The study concludes that Pergulaan Village has continuously adapted to historical, administrative, and economic transformations, indicating that its historical narrative is better understood as a history of rural social change rather than merely a history of plantation development.